The theology of creation in Vito Mancuso’s Radical Theology - C. C. Simut (Acta Theologica)
Vito Mancuso, a young Italian theologian of lay inspiration, has been causing a great deal of theological unrest within Italy’s conservative quarters because of his radical program intended to re-found Christianity in order for it to be understood by contemporary men and women. Mancuso’s concern to re-anchor Christian theology in the experience of today’s people drove him to affirm the fundamental importance of matter as source of everything. Thus, matter is the mother of all existing realities which include the universe, nature and even the soul. In other words, Mancuso proposes a theology from below which seeks to re-interpret the basic teachings of Christianity in a way which sheds light on the experience of today’s world. This theological program includes the traditional doctrine of creation, which in Mancuso acquires a new facet as it is described in terms related to his conviction that the origin of everything should be understood in material terms.